Phonological awareness and quick naming of developmental dyslexia in Sekolah Dasar Inklusif Pantara, Jakarta - Yanti Br Sitepu (English, 2018)
The weak phonological awareness and slow reaction time in word identification is a disorder that dyslexic people have in reading (Wolf and Bowers, 1999). Therefore, this study will investigate the ability of phonological awareness (phonological awareness), rapid naming (Rapid Naming) and reading ability of people with dyslexia. The subjects consisted of 4 children aged 7-8 years of dyslexia in Pantara Inclusive Elementary School, Jakarta. The four dyslexic children were compared to the control group (20 children from Kwitang 8 PSKD Pancoran Mas, Depok, who had the same age and gender as dyslexic children). The research used quantitative method with case study control design. The study was conducted with three experiments, namely: reading test, counting the number of silabel, and fast-track test. The first experiment consisted of 100 words (simple words, digraphs, diphthongs, and consonant clusters). The second experiment consisted of 48 words (24 words with illustrations and 24 words with trisilabik). All words are from the 10,000 words that have the highest frequency in the Indonesian linguistic corpus (Indonesianwac). The third test is 50 RAN letters (Pennington et al., 2001). Results showed that persons with dyslexia had a lower ability than the control group on all three tests. Dyslexic children tend to perform sound recovery, eliminate phonemes and swap words with nonwords and slow reaction times. Based on the results obtained, 2 dyslexic children data support double deficit hypothesis Wolf and Bowers (1999) because dyslexic children show phonological deficits and rapid naming deficits.